2021
DOI: 10.3390/molecules26164729
|View full text |Cite
|
Sign up to set email alerts
|

Iloprost Attenuates Oxidative Stress-Dependent Activation of Collagen Synthesis Induced by Sera from Scleroderma Patients in Human Pulmonary Microvascular Endothelial Cells

Abstract: Endothelial cell injury is an early event in systemic sclerosis (SSc) pathogenesis and several studies indicate oxidative stress as the trigger of SSc-associated vasculopathy. Here, we show that circulating factors present in sera of SSc patients increased reactive oxygen species (ROS) production and collagen synthesis in human pulmonary microvascular endothelial cells (HPMECs). In addition, the possibility that iloprost, a drug commonly used in SSc therapy, might modulate the above-mentioned biological phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…SSc patients have a chronic hypoperfusion that improves after Iloprost infusion, both in the skin and in the internal organs [ 8 , 9 ]. Furthermore, Iloprost has been shown to have a long-lasting endothelium protective effect [ 11 ]. Prolonged hypoperfusion contributes to activation of inflammatory signals and oxidative stress, thereby accelerating injury and fibrosis in skin and kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSc patients have a chronic hypoperfusion that improves after Iloprost infusion, both in the skin and in the internal organs [ 8 , 9 ]. Furthermore, Iloprost has been shown to have a long-lasting endothelium protective effect [ 11 ]. Prolonged hypoperfusion contributes to activation of inflammatory signals and oxidative stress, thereby accelerating injury and fibrosis in skin and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Iloprost induces vasodilation, anti-platelet aggregation, cytoprotection, antioxidant effect and immunomodulation. These effects ameliorate the small vessel vasculopathy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These oxidative molecules not only induced oxidative stress but enhanced collagen synthesis by human pulmonary smooth muscle cells [ 124 ]. Recently, Giordo et al [ 125 ] found that Iloprost (a stable analog of prostacyclin) could attenuate SSc serum-induced collagen synthesis by human pulmonary microvascular-endothelial cells via anti-oxidant mechanisms.…”
Section: The Molecular Basis Of Accelerated Inflamm-aging In Patients With Sscmentioning
confidence: 99%
“…Of note, treatment with TAK1 inhibitor HS‐276 prevented dermal and pulmonary fibrosis and reduced the expression of profibrotic mediators in bleomycin‐treated mice 167 . Among antioxidants, NAC showed therapeutic benefit in a subset of patients with PSS 168,169 and ILD 170–172 . Iloprost, a stable analog of PGI2, is an established therapy for skin and pulmonary manifestations in patients with PSS.…”
Section: Introductionmentioning
confidence: 99%